Audience reconstructed: social media interaction by BTS fans during live stream concerts - Upham, Finn; Lee, Jin Ha; Park, So Yeon (Frontiers in Psychology, 2024)
COVID-19-motivated social distancing made online concerts common practice in 2020 and 2021,with millions logging into streaming sites to see their favourite artists perform in realtime. For some fans, watching alone at home may have been enough, but concert-concurrent surges of social media activity suggest many virtual performance attendees are doing more. To understand why fans would turn their attention from these precious performance streams to social media, we explored Twitter engagement during four live streamed concerts performed by the Kpop group BTS in 2021. In public Tweets sampled by either concert hashtag or predefined stream of users and keywords, we found consistent patterns in the relative posting rates during concert program events. Short Shout Tweets clustered at the start of songs, while the rate of Retweets often fell during musical performances and shot up when BTS was off stage. Concert attendees used Twitter to share their own excitement and check in with others in the audience. We also investigated these concert-related Tweets by studying the content and tone of subsamples selected by popularity (number of Retweets during the concert). This analysis suggests that the materials most widely shared were informational or featured concert visuals, mimicking how fans use their phones at in-person pop shows. Most original posts, with few Retweets, were more personal and expressive of admiration for the performers. Comparison between the samples (concert hashtag vs stream) also suggests users were strategic in using or omitting official concert hashtags with the strongest differences in the most widely disseminated content. Postings on Twitter during these performances seemed principally directed to fellow fans and audience members. By leveraging their existing social media networks, these concert attendees constructed a collective and interactive concert space, connecting with friends and strangers in the crowd and helping each other capture a richer experience than any broadcasting platform currently supports.